The men who swallowed the sun - Abū Julayyil, Ḥamdī (Hoopoe, 2022)
"Two Bedouin men from Egypt's Western Desert seek to escape poverty through different routes. One-the intellectual, terminally self-doubting, and avowedly autobiographical Hamdi-gets no further than southern Libya's fly-blown oasis of Sabha, while his cousin-the dashing, irrepressible Phantom Raider-makes it to the fleshpots of Milan. The backdrop of this darkly comic and unsentimental story of illegal immigration is a brutal Europe and Muammar Gaddafi's rickety, rhetoric-propped Great State of the Masses, where "the Leader" fantasizes of welding Libyan and Egyptian Bedouin into a new self-serving political force. Compelling and visceral, with a seductive, muscular irony, The Men Who Swallowed the Sun is an unforgettable novel of two men and their fellow migrants and the extreme marginalization that drives them."--